Endoscopic Medial Rectus Sling: A Window Into the Intraconal Orbital Apex. Issue 3 (May 2016) - Shafi, Fariha; Zaidi, Syed; Mehta, Purnima; Ahluwalia, Harpreet Singh; Ahmed, Shahzada K.
Abstract : Purpose: Surgical approaches to the medial orbit especially within the cone of orbital muscles necessitate great precision and care to avoid damage to surrounding structures—most importantly the optic nerve. The authors present a novel technique in which access to the medial orbital contents was achieved through an entirely endoscopic approach. Methods: A 72-year-old Caucasian female presented with loss of vision in the right eye and reduced extraocular movements. Baseline blood tests were within normal limits. Inflammatory markers were slightly elevated. CT scan revealed bilateral medial orbital apex masses. Biopsy of the right orbital apex lesion was performed through an exclusively endoscopic approach in which the medial rectus muscle was retracted infero-medially. Results: This exclusively endonasal approach to the medial intraconal space provided excellent access to the orbital apex, thus allowing successful biopsy of the medial orbital apex lesion. A video of the surgical technique demonstrates its use in this patient (see Video, Supplemental Digital Content 1, available athttp://links.lww.com/IOP/A123 ). Conclusions: Similar reports of endonasal medialization of the medial rectus for accessing intraconal orbital lesions have been previously described in the rhinological literature. The authors describe a modification that allows for a safe and less invasive approach to the medial intraconal space and intraorbital optic nerve. There is minimal trauma to the surrounding tissues and no further damage to the optic nerve along with no associated adverse clinical sequelae. In addition, this negates the need for an adjuvant external or transconjunctival approach. Abstract : The endoscopic medial rectus sling is a safe and effective technique for accessing medial orbital apex lesions without needing an adjuvant external or transconjunctival approach.Supplemental Digital Content is available in the text.